Cloning and transformation of rbc L gene in Solanum melongena L. - Singh, Ram Pal; Singh, Ompal; Mukesh, Mukesh (Recent Research in Science and Technology, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Plants would not able to undergo photosynthesis without rubisco, which is a powerful tool in phylogenic analysis, species diversity estimates, varietal identification and population analysis. Transformation is a parasexual method of introducing new genes into an organism. pGEM- T and pGEM –T easy vector, containing multiple cloning region, flanked by recognition sites for the restriction enzyme EcoR1 and Not I, are employed for cloning PCR product and to transform bacterial strain E. coli JM- 109 which is deficient in B- galactosidase activity due to deletion in both genomic and episomal copies of lacZ gene. Ampr and lacZ gene are used for recombinant selection. On the other hand cloning of the gene for sequence divergence amongst species and genera is also a powerful tool in comparison to direct sequencing of PCR product. The rbcL isolated from two cultivars indigenous (A) & exogenous (B), separately. In both the cultivars the sequence of rbcL gene found more or less similar either cultivars taken from greenhouse (A)or from field (B). after sequencing, rbcL probe may be used for screenable related taxa as well as the taxa which have the low photosynthetic rate, the insertion of rbcL gene through recombinant DNA technology or other recent similar technologies, in higher amount may increase photosynthesis rate. Resulting this the crop may be improved either for qualitative or quantitative traits.